Sephardic Jewry and Mizrahi Jews - Medding, Peter Y. (Studies in contemporary Jewry ;, 2007)
Sephardic Jewry and Mizrahi Jews offers a collection of new scholarship on the issues of self-definition and identity facing Sephardic Jewry. The essays draw on a variety of disciplines--demography, history, political science, sociology, religious and gender studies, anthropology, and literature. Contributors explore the issues surrounding the emergence and increasingly wide usage of "Mizrahi" in place of "Sephardic," as well as the invigoration of Sephardic Judaism. They look at the evolution of Sephardic politics in Israel through the dramatic rise and continuing influence of the Shas political party and its spiritual leader, Rabbi Ovadia Yosef. Other contributors examine the variegated nature of Mizrahi immigration to Israel, fictional portraits of female Mizrahi immigrants to Israel in the 1940s and 1950s, contemporary Mizrahi Israel feminism, modern Arab historiography's portrayal of Jews of Muslim lands, and the changing Sephardic halakhic tradition. --From publisher's description